(untitled) (Al-Qamar, 2023)
Culture is the foundation of human life and the identity of any nation or society. Nations that advance in the cultural field experience progress and success. Today’s era is actually a time of cultural clash and competition, so it is necessary that we get acquainted with this culture. Will point to civilization and culture, which means the customs and manners that dictate our lives and yours. Civilization and culture mean our faith and beliefs and all the beliefs and ideas that are involved in our individual and social lives. Islamic culture is a standard culture that has the highest values and standards for a society and for any group of human beings. It can put any society on the path of progress and prosperity by making it proud and dignified. The Muslim Ummah is made up of different nations, races, and schools of thought. The oldest civilizations and vast cultures flourished in the same areas where Muslims live today. This diversity, this colorful style, and this ownership of the sensitive areas of the planet are the main characteristics of the Muslim Ummah. The common heritage of history and culture can further increase the strength of this Ummah. In this article, Dr. Naseer Ahmad Nasir’s views on Islamic culture are described. Dr. Sahib has described the source of Islamic culture as the Quran and Sunnah. The aesthetic color of Islamic culture has been described.